The Science-Religion Conflict and the Difficulty of Accepting Novelties - Pons, Santiago (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the 19th century, the conflict thesis was forged to explain the science-religion relationship. This thesis presents religion as an obstacle to the development of science. Andrew White publishes a book that is at the origin of this thesis and Charles S. Peirce writes a review of this book in which he shows that there is nothing in religion that opposes scientific progress, but points to four human characteristics that offer difficulties in the face of radical novelties. It is interesting to note how while the conflict thesis was forged, one of the greatest thinkers already shows the weakness of this thesis.